Emerging Adults and Recovery Capital: Barriers and Facilitators to Recovery. Issue 2 (April 2018) - Elswick, Alex; Fallin-Bennett, Amanda; Ashford, Kristin; Werner-Wilson, Ronald
Abstract: Introduction: Substance use disorders (SUDs) are chronic, relapsing brain disorders associated with morbidity, mortality, and high healthcare costs. Emerging adults are particularly vulnerable, with twice the risk of developing an SUD relative to their adult or adolescent counterparts. Emerging adults in addiction and recovery are understudied. Accordingly, the concept of recovery capital has been developed to account for the internal and external resources that an individual can mobilize to recover from an SUD. To better understand the barriers that contribute to relapse, we explored recovery capital among emerging adults. The aims of this phenomenological study were to explore and describe the experience of emerging adults in recovery and to identify the barriers and facilitators to their recovery. Methods: The informants ( n = 8) were 18–25 years old in recovery from SUDs. Data were collected in 2016 using semistructured interviews and subsequently analyzed in 2017 for emerging themes. Results: Informants in this study reported challenges that may be unique to their age and stage of development. Informants reported residential and financial instability as barriers to recovery. Alternatively, informants reported spirituality and visible role models in recovery as facilitators of recovery. Finally, informants reported that the role of their families changed temporally throughout the course of their addiction to facilitate their recovery. Conclusion: The results from this study suggest that the developmental tasks facing emerging adults are exacerbated in addiction and recovery, which increases the likelihood of SUD relapse.